Comparative efficacy and safety of non-pharmacological interventions on treatment-induced xerostomia in head and neck cancer patients: a systematic review and network meta-analysis - Jingyu Tai; Aimin Guo; Juntong Chen; Haoyu Li; Qian Dong; Wumei Hao; Wenjing Wang; Zunzhu Li; Jianshu Ye; Jinbang Liu; Chengwu Yang (Frontiers in Oncology, 2025)
AimTo comprehensively evaluate the efficacy and safety of non-pharmacological interventions for radiotherapy-induced xerostomia in patients with head and neck cancer.MethodsA systematic literature search was conducted in PubMed, Embase, the Cochrane Library, and Web of Science for articles published up to March 1, 2025. Three outcome measures were utilized to assess treatment effectiveness: xerostomia, saliva flow rate, and xerostomia-related quality of life. A Bayesian network meta-analysis was employed to synthesize the comparative performance of different non-pharmacological interventions. The study protocol was registered in the PROSPERO database (CRD420251027019).ResultsA total of 30 RCTs encompassing 1,595 participants and nine distinct non-pharmacological treatment modalities were included. Compared with the SOC, mouthwash demonstrated the most pronounced improvement in XQ (SMD = -0.70; 95% CI: -1.38 to -0.01) and XI scores (SMD = -0.68; 95% CI: -1.09 to -0.26). Oral moisturizing gel exhibited the greatest reduction in VAS scores (SMD = -1.55; 95% CI: -2.31 to -0.80). Regarding salivary flow enhancement, oral moisturizing gel was most effective in increasing USFR (SMD = 3.83; 95% CI: 0.56 to 7.09), while chewing gum provided the highest gain in SSFR (SMD=3.66; 95%CI: -0.08 to 7.41). Among safety outcomes, electrical stimulation therapy was associated with the most favorable profile relative to SOC (SMD = -1.82; 95% CI: -3.96 to 0.33).ConclusionsNon-pharmacological interventions appear to offer superior efficacy with comparable safety to SOC in care of radiotherapy-induced xerostomia among patients with head and neck cancer. Mouthwash is likely the most effective option for alleviating subjective xerostomia symptoms, with oral moisturizing gel as a valuable alternative. For salivary flow enhancement, oral moisturizing gel is preferred for unstimulated flow, whereas chewing gum is optimal for stimulated flow. Electrical stimulation therapy may yield the most substantial improvement in quality of life, with photobiomodulation therapy representing a promising adjunctive strategy.Systematic review registrationProspective Register of Systematic Reviews (PROSPERO), identifier CRD420251027019.